MODEL CONTEXTUAL TEACHING AND LEARNING DAN HASIL BELAJAR IPA PADA TEMATIK TERPADU - Putri Latifah; Hendrizal (Jurnal Riset Pendidikan Dasar Dan Karakter, 2019)
This research is motivated by student learning outcomes that are still low with problems namely: in learning students are less able to find themselves and solve the problems provided, lack of cooperation and student responsibility because students are still unable to provide answers to the questions given by the teacher, and students are less active in discussions with friends. This study aims to determine the effect of the Contextual Teaching And Learning (CTL) model on Natural Science Learning Outcomes in Integrated Thematic Learning in Class V SDN 32 Tanjung Bonai Tanah Datar District. This type of research is Quasi Experimental Design, with a Posttest Only Control Design research design. The population of this study was all students of class V of SDN 32 Tanjung Bonai in the academic year 2019/2020 with a sample of VA and VB class students of 39 students. Collecting data in this study is to use a test of learning outcomes in the form of objective questions totaling 17 items, the data obtained were analyzed using the t test. Based on data analysis, the results of hypothesis testing with the t-test were obtained and showed tcount = 7.820 and ttable = 1.687 with dk = 39 (n1 + n2 - 2 = 21 + 18-2 = 37) and a 5% significance level. Based on testing tcount> ttable (7,820> 1,687). So it can be concluded "There is a significant influence with the use of the Contextual Teaching And Learning (CTL) model of science learning outcomes in integrated thematic learning in class V SDN 32 Tanjung Bonai in the 2019/2020 school year".